Divergent perspectives: autistic adults' perceptions of the police. Issue 3 (3rd March 2022) - Parry, Megan M.; Huff, Jessica
Abstract : Purpose: Much of the current criminological research regarding police and the autistic community focuses on police training for interacting with autistic individuals or the experiences, fears and perceptions of parents or caregivers. Largely absent from the criminological research are the opinions and perceptions of autistic adults. The purpose of the paper is to examine perceptions of the police and police-led initiatives among these individuals. Design/methodology/approach: The authors analyze data from 121 autistic adults regarding their perceptions of the police and police-led autism awareness efforts using ordinary least squares (OLS) regression. Variables of interest include perceptions of procedural justice, police treatment of autistic individuals, fear of interacting with police and perceptions of police autism awareness campaigns. Findings: Findings indicate that autistic respondents vary in perceptions of the police. Prior negative experiences with police have a stronger influence on perceptions than do positive experiences. Support for awareness campaigns is also varied. Originality/value: Despite high-profile police incidents involving autistic individuals, there have been no empirical examinations of autistic adults' global perceptions of the police or police-led autism awareness campaigns. The current study addresses that oversight by directly examining autistic adults' perceptions. The approach is particularly salient given the ongoing police public scrutiny surrounding officer interactions with individuals from special populations, which is largely uninformed by research centering the voices of impacted individuals.